Altitude profile of the effective radius of atmospheric boundary layer aerosols retrieved from simultaneous two-wavelength lidar measurement - Galvez, Maria Cecillia D. (Animo Repository, 2001)
The altitude profile of the effective radius, reff, of atmospheric boundary layer aerosols was retrieved from simultaneous two-wavelength lidar measurement near Manila Bay. The effective radius was retrieved using a simple method that makes use of the angstrom coefficient, δ, obtained from the extinction coefficients at the two wavelengths. The altitude profiles of the extinction coefficients at 532-nm and 1064-nm lidar wavelengths were obtained using Fernald's inversion algorithm combined with Klett's boundary value algorithm, used to obtain the aerosol extinction coefficient at the reference height. Assuming a lognormal size distribution, with a geometric standard deviation of 1.54, for atmospheric boundary layer aerosols, and a constant refractive index of 1.45 - 0i, the angstrom coefficient is determined at different mode radius, rg, using Mie Scattering Theory. A curve fitting analysis using the method-of-least-squares is done on the theoretical value of δ to obtain a sixth-order polynomial equation flint gives the dependence of δ with rg. The altitude profile of reff is retrieved by using the measured value of δ into the equation. This method was applied to actual lidar experiments and the effective radius of the atmospheric boundary layer aerosols was observed to vary between 0.26 μm to 0.29 μm within the layer.